2014
DOI: 10.1002/2013jd020996
|View full text |Cite
|
Sign up to set email alerts
|

Annual distributions and sources of Arctic aerosol components, aerosol optical depth, and aerosol absorption

Abstract: Radiative forcing by aerosols and tropospheric ozone could play a significant role in recent Arctic warming. These species are in general poorly accounted for in climate models. We use the GEOS-Chem global chemical transport model to construct a 3-D representation of Arctic aerosols and ozone that is consistent with observations and can be used in climate simulations. We focus on 2008, when extensive observations were made from different platforms as part of the International Polar Year. Comparison to aircraft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
105
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 141 publications
15
105
1
Order By: Relevance
“…The major transport pathway of North American emissions to the Arctic follows constant potential temperatures, which cause cloud formation and precipitation, hence higher wet scavenging of aerosols. Brock et al, 2011, McConnell, 2007, Stohl, 2006, Breider et al, 2014and Liu et al, 2015 show similar low contributions of North American Anthropogenic emission to the Arctic surface concentration. Less than 5% percent of emissions are transported from each of South Asia and the Middle East to the Arctic.…”
Section: Geographical Source Contribution To Pm Concentrationmentioning
confidence: 80%
See 1 more Smart Citation
“…The major transport pathway of North American emissions to the Arctic follows constant potential temperatures, which cause cloud formation and precipitation, hence higher wet scavenging of aerosols. Brock et al, 2011, McConnell, 2007, Stohl, 2006, Breider et al, 2014and Liu et al, 2015 show similar low contributions of North American Anthropogenic emission to the Arctic surface concentration. Less than 5% percent of emissions are transported from each of South Asia and the Middle East to the Arctic.…”
Section: Geographical Source Contribution To Pm Concentrationmentioning
confidence: 80%
“…However, 10 during the past two decades emissions from East Asia have increased rapidly due to the vast economic growth, while the emissions from Europe have declined during the same time period (Streets et al, 2009). Recent studies have shown the significant contribution of Asian emissions to the Arctic, especially during winter-spring (Breider et al, 2014;Fisher et al, 2010;Koch and Hansen, 2005;Shindell et al, 2008;Stohl, 2006;Wang et al, 2011).…”
mentioning
confidence: 99%
“…Stohl, 2006;Shindel et al, 2008;Hirdman et al, 2010;Wang et al, 2014) while others found eastern and southern Asia had the largest contribution (Koch and Hansen, 2005;Ikeda et al, 2017). Some studies suggested that Europe was the dominant source of BC aloft (Stohl, 2006;Huang et al, 2010b) while others found eastern and southern Asia was the most important source (Sharma et al, 2013;Breider et al, 2014;Wang et al, 2014;Ikeda et al, 2017) in the middle troposphere. Recent work by Stohl et al (2013) and Sand et al (2016) raised questions about prior studies by identifying the importance of seasonally varying residential heating and by suggesting a significant overlooked source from gas flaring in high-latitude regions.…”
Section: Introductionmentioning
confidence: 97%
“…We subsequently use the adjoint of the GEOS-Chem model to investigate the spatially resolved sensitivity of Arctic BC column concentrations to global emissions. Our work builds on knowledge gained from previous GEOS-Chem studies of Arctic BC (Wang et al, 2011;Breider et al, 2014Breider et al, , 2017Qi et al, 2017a, b) with major improvements, including (1) new airborne measurements during 2009, 2011 and 2015 when more typical fires than in previous studies foster better understanding of anthropogenic source contributions to the Arctic; (2) new refractory BC (rBC) measurements in the Arctic more accurately constrain emissions in simulations; (3) more recent and improved emissions better represent the global redistribution of BC emissions and include flaring and seasonal emissions of residential heating; and (4) seasonal source attribution using the adjoint of GEOS-Chem reveals the importance of specific sources. Bond et al (1999) and is further reduced by 30 % at all stations following Sinha et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Long range transport could also have brought Saharan dust to the region (e.g. Breider et al, 2014), and this was seen during the Spring campaign of the ACCACIA project 15 (Young et al 2016b), though the temperature of the clouds reported here did not go below -12 °C and so any dust particle present would likely not act as INP.…”
Section: Potential Sources Of Aerosol/in For This Projectmentioning
confidence: 76%